Changes in the biomass and dominant feeding mode of benthic assemblages with depth off Livingston Island (Antarctica) - Saiz-Salinas, José Ignacio; Ramos, Ana; Munilla, Tomás; Rauschert, Martin (Polar Biology, 1998)
To elucidate spatial assemblage patterns during 2 consecutive austral summer seasons, we sampled intensively the macrofauna from 73 stations located at the southern coast of Livingston Island. Representatives of 28 higher taxonomic groups were used for the faunal analysis. While two faunal descriptors (i.e. group richness and total biomass) changed markedly with increasing water depth, total density remained relatively constant. Sessile suspension-feeders belonging to the Ascidiacea and Porifera dominated at shallower depths (<100 m) with a mean biomass (wet weight) estimate of 3,238 g m−2. In contrast, deeper faunal assemblages were dominated by deposit-feeding polychaetes with lower biomass values of 538 g m−2. Mean body mass for dominant groups reflected two contrasting trophic strategies: ascidians at shallower depths (<100 m) attained a value of 6 g whereas a comparable density of polychaetes at deeper depths (>100 m) obtained 0.37 g. This faunal discontinuity, primarily influenced by depth-related variables, is suggested to be directly related to food availability. SI